THE IMPLEMENTATION OF MULTIMEDIA-ASSISTED MATHEMATICAL HABITS OF MIND TO IMPROVE STUDENTS CRITICAL THINKING - Lukman Ibrahim; Budi Azhari; Cut Rina Rossalina (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
One of the current educational goals is to train students to communicate in the teaching and learning process and have the skills to think in enhancing learning outcomes, one of which is critical thinking skills. This study aimed to compare students' critical thinking skills taught by multimedia-assisted mathematical habits of mind (MHM) learning strategies and those taught by conventional learning strategies for students at SMPS Ummul Ayman Samalanga. It uses a quasi-experimental method. The population of this study is all grade 8 students at the Private Yunior High School (SMPS) Ummul Ayman Samalanga. Two classes of grade 8 were randomly selected as experimental and control groups. Data was collected by using pre-test and post-test procedures. The results of data analysis by using the independent samples t-test showed that the value of t-observation is 9.53 and the value of t-table is 1.68. So, because the value of t-observation is greater than the value of t-table, it can be concluded that students' mathematical critical thinking skills taught by MHM learning strategies are better than the critical thinking skills of those taught by conventional learning strategies. The conclusion can be reached because the instruction in the experiment class motivated students to be more active in reconstructing teaching materials individually and in pairs.